The re-invention of the European radical right : populism, regionalism, and the Italian Lega Nord - Zaslove, Andrej, 1963- (McGill-Queen's University Press, 2011)
"Political commentators were surprised at the re-emergence of right-wing parties in Western Europe in the 1970s and early 1980s given that right-wing extremists had largely disappeared from successful electoral politics after the end of the Second World War. Since their resurgence, such parties have become permanent fixtures across Europe. The Re-invention of the European Radical Right examines what accounts for their initial rise and their continued success as well as how they should be classified: are they fascist, neo-fascist, radical, extreme, or populist? Combining an in-depth case study of the Italian Northern League with a comparative focus on other parties, Andrej Zaslove employs a socio-economic, institutional, and ideological analysis to argue that the new wave of right-wing parties in Western Europe converged into a radical right populist party family in the 1990s. He examines the transformation of the Northern League from its regionalist roots while focusing on the party's nationalism, authoritarianism, support for a market economy, opposition to globalization, and scepticism regarding Italian integration into the European Union. He also scrutinizes the Northern League's participation in political power between 2001 and 2006 and its influence on federalism, immigration, economic policy, and European integration. A thorough and thought-provoking work, The Re-invention of the European Radical Right offers remarkable insight into the ongoing effects of radical right populism on politics and public policy in Europe."--